Inventory management for essential oil UMKM: enhancing business performance with data mining - Luky Fabrianto; Johan Hendri Prasetyo; Novianti Madhona Faizah; Susi Solichatun (Jurnal Mantik, 2023)
Micro, small, and medium enterprises (UMKM) play a critical role in driving economic growth and employment opportunities in Indonesia. PT Sukacita Kokoh Bersama (SKB), a company specializing in essential oil sales, exemplifies the dynamic nature of UMKM by embracing technological advancements to thrive in the competitive market. To address the challenge of optimizing inventory management, SKB implemented data mining techniques, specifically the Apriori algorithm, to uncover hidden relationships among different oil types and gain insights into consumer preferences and purchasing behavior. The study aimed to identify relevant sales patterns and predict demand for each oil type. With a threshold of 30%, several rules were generated, including "If customers purchase Lavender Oil and Lemon Oil together, there is a 53% confidence that they will also purchase Peppermint Oil". This research showcases the importance of data mining in enhancing inventory management and decision-making processes for UMKM like SKB.